EARTH TREMORS - EMERGING THREATS IN NORTHERN NIGERIA - Oyibo, David; Kadiri, Afegbua Umar (FUDMA JOURNAL OF SCIENCES, 2023)
The August 2000 Jushi Kwari, September 2016 Kwoi Kaduna, and September 2018 Mpape (Abuja) seismic events have clearly placed Nigeria's Northern states at high risk of earth tremors. Although the Northern part of Nigeria is far from earthquake-prone zones around the world, recent seismic activity in the region suggests that Northern Nigeria is now vulnerable to earthquakes. As a result, the purpose of this research is to identify the vulnerability and assess the evolution of tremor activities in Nigeria's Northern States. Previous research has revealed dominant NE-SW and NW-SE trending structures distributed throughout Northern Nigeria, with all major regional fault lines (Romanche, Chain Charlot, and St Paul) extending from the Atlantic Ocean linked to NE-SW and SW faults, which are interpreted as conduits of seismic energy that cause earth tremors in Nigeria.